Front Cover: C−C Coupling through Nitrogen Deletion: Application to Library Synthesis (Chem. Eur. J. 4/2023). Issue 4 (30th December 2022) - Holovach, Serhii; Melnykov, Kostiantyn P.; Poroshyn, Illia; Iminov, Rustam T.; Dudenko, Dmytro; Kondratov, Ivan; Levin, Mark; Grygorenko, Oleksandr O.
Abstract : Good chemistry, like great music, sometimes needs a good collaboration. The Cover Picture shows a combination of nitrogen‐deleting anomeric amide power (discovered by Levin's group from the University of Chicago) and parallel synthesis capabilities of Ukrainian chemists, which resulted in a combinatorial library obtained through formal C( sp 3 )–C( sp 3 ) coupling and a unique synthetically accessible chemical space of nearly 600 K representatives. Background photo by Kristina Krynytska. More information can be found in the Research Article by O. O. Grygorenko and co‐workers. (DOI: 10.1002/chem.202203470 ).